Take Care of the Heart to Prevent Hypertension: Community Service to Increase Awareness and Control Hypertension - Ahmadi; Mei Lestari Ika Widyyati (Indonesian Journal of Society Development, 2023)
Hypertension is one of the dangerous conditions because it is a risk factor for causing health complications. The purpose of this service is carried out to increase public awareness of the importance of controlling hypertension so that it does not cause complications in the future. This service is carried out by means of health counseling, blood pressure checks and the provision of medicines needed by participants. the time of implementation of activities on December 19, 2022. With the background of the participants of community service activities are retirees from civil servants within the Sampang Regency Government as many as 22 participants. The results of the service were obtained that most participants experienced asymptomatic hypertensive events so that routine checks were needed for participants so that they could identify early the risk of hypertension. Continuous education is important so that awareness and prevention of hypertension are carried out properly and there is an increase in understanding of hypertension and its treatment